Safety and Oncological Outcomes of Laparoscopic NOSE Surgery Compared With Conventional Laparoscopic Surgery for Colorectal Diseases: A Meta-Analysis - Liu, Rui-Ji; Zhang, Chun-Dong; Fan, Yu-Chen; Pei, Jun-Peng; Zhang, Cheng; Dai, Dong-Qiu (Frontiers in Oncology, 2019)
ABSTRACT Objective: To evaluate the safety and oncological outcomes of laparoscopic colorectal surgery using natural orifice specimen extraction (NOSE) compared with conventional laparoscopic (CL) colorectal surgery in patients with colorectal diseases. Methods: We conducted a systematic search of PubMed, EMBASE and Cochrane databases for randomized controlled trials (RCTs), prospective nonrandomized trials and retrospective trials up to September 1, 2018, and used 5-year disease-free survival (DFS), lymph node harvest, surgical site infection, anastomotic leakage, and intra-abdominal abscess as the main endpoints. Subgroup analyses were conducted according to the diﬀerent study types (RCT and NRCT [nonrandomized control trial]). A sensitivity analysis was carried out to evaluate the reliability of the outcomes. RevMan5.3 software was used for statistical analysis. Results: Fourteen studies were included (two RCTs, seven retrospective trials and five prospective nonrandomized trials) involving a total of 1435 patients. Compared with CL surgery, the NOSE technique resulted in a shorter hospital stay, shorter time to first flatus, less postoperative pain, and fewer surgical site infections and total perioperative complications. Anastomotic leakage, blood loss and intra-abdominal abscess did not differ between the two groups, while operation time was longer in the NOSE group. Oncological outcomes such as proximal margin (weighted mean difference [WMD]=0.47; 95% confidence interval [CI] −0.49 to 1.42; P=0.34), distal margin (WMD= −0.11; 95% CI −0.66 to 0.45; P=0.70), lymph node harvest (WMD= −0.97; 95% CI −1.97 to 0.03; P=0.06) and 5-year DFS (hazard ratio=0.84; 95% CI 0.54 to 1.31; P=0.45) were not different between the NOSE and CL surgery groups. Conclusions: Compared with CL surgery, NOSE may be a safe procedure, and can achieve similar oncological outcomes. Large multicenter RCTs are needed to provide high-level, evidence-based results in NOSE-treated patients and to determine the risk of local recurrence.